Desarrollo de un plan de marketing en salud para la Clínica Santa Marianita de Jesús de la ciudad de Quito - Morales Marín, Andrea Carolina (2017)
This research work has the purpose of proposing a marketing plan focused on certain strategies based on the needs of the internal customer and the external customer. To identify the basis of the needs, an analysis of the situation in which the institution was found was carried out by carrying out a SWOT and a PEST analysis that help to better understand the situation of this research. A quantitative methodology has been used, two types of surveys have been developed for the different participants in this research based on previous models used in different health institutions. Through the surveys implemented, it was possible to identify the needs of the internal customer, as follows: Improve economic compensation, increase recognition, and improve the working environment and internal communication. While for the external customer were improving the public image of the institution and increase advertising. Finally, a marketing plan was developed based on specific strategies to meet the needs of the two clients, taking into account the endomarketing model and the corporate image.